EFEITO DO GEL DE ASCORBIL FOSFATO 3% NA RESISTÊNCIA DE UNIÃO DA RESINA COMPOSTA AO ESMALTE CLAREADO COM PERÓXIDO DE HIDROGÊNIO 35%. - CASTRO, Milena de Fátima Schalcher de (2012)
The aim of this in vitro study was to evaluate the effect in different times of 3% phosphate ascorbyl gel (PA), onto the microshear bond strength of composite resin (CR) to bovine enamel treated with 35% hydrogen peroxide (HP). Thirty bovine incisors were selected. Thirty enamel blocks of 70mm2 were made and distributed into 5 groups (n = 6), which were made on three specimens (n = 18), according to treatment: G1: No bleaching + CR; G2: HP + CR after 15d; G3: HP + CR after 24h; G4: HP + PA 15m + CR after 24h; G5: HP + PA 2h + CR after 24h. The resin cylinders were filled with Filtek ™ Z-350 by Tygon matrices, with photoactivation of 40s. The specimens were stored with cotton soaked in distilled water at 37 ° C for 24h. Microshear bond strength test was performed using universal testing machine with a 50N load at a speed of 0.5 mm / min. Fracture modes were assessed by a stereomicroscope 40x. Microshear bond strength values were submitted to the ANOVA one way and Tukey test (p <0.05). G1 had the highest mean bond strength (15.52 ± 10.01 MPa) when compared to the G3 (5.76 ± 8.02 MPa) and G5 (4.78 ± 4.39 MPa) (p <0.01). However the other groups, G2, G3, G4 and G5 showed no significant differences between groups (p> 0.05). Failure modes were divided into adhesive and mixed, showing mainly adhesive failure (90%) in all groups. It was concluded that 3% phosphate ascorbyl gel applied in time of 15 minutes was able to improve the bond strength of composite resin to bleached bovine enamel.